Pengaruh Independensi, Profesionalisme, Tingkat Pendidikan Dan Pengalaman Kerja Terhadap Kinerja Auditor (Studi Empiris Pada Badan Pemeriksa Keuangan Republik Indonesia (BPK RI) Perwakilan Provinsi Lampung) - Wulansari, Dewi; Hendri, Nedi; Rahayu, Sri Retnaning (Expensive: Jurnal Akuntansi dan Keuangan, 2022)
This study aims to determine the Effect of Independence, Professionalism, Education Level and Work Experience on Auditor Performance (Empirical Study at the Supreme Audit Agency of the Republic of Indonesia (BPK RI) Representative of the Province of Lampung). Data obtained from the results of the questionnaire respondents totaling 93 people. This study uses data analysis techniques, classical assumption tests and hypotheses. The type of research used is quantitative. The results showed that independence, professionalism, education level and work experience had a significant positive effect on auditor performance.